2004
DOI: 10.1172/jci200421134
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin inhibits leptin- and activation-induced proinflammatory cytokine expression by human monocytes and T cells

Abstract: Ghrelin, a recently described endogenous ligand for the growth hormone secretagogue receptor (GHS-R), is produced by stomach cells and is a potent circulating orexigen, controlling energy expenditure, adiposity, and growth hormone secretion. However, the functional role of ghrelin in regulation of immune responses remains undefined. Here we report that GHS-R and ghrelin are expressed in human T lymphocytes and monocytes, where ghrelin acts via GHS-R to specifically inhibit the expression of proinflammatory ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
220
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 663 publications
(229 citation statements)
references
References 50 publications
8
220
1
Order By: Relevance
“…We have previously demonstrated that, similar to their opposing metabolic effects on food intake, leptin and ghrelin also exert reciprocal regulatory effects on proinflammatory cytokine production (12). Ghrelin inhibits activation-and leptin-induced proinflammatory cytokine production by human T cells and monocytes (12).…”
Section: And E)mentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that, similar to their opposing metabolic effects on food intake, leptin and ghrelin also exert reciprocal regulatory effects on proinflammatory cytokine production (12). Ghrelin inhibits activation-and leptin-induced proinflammatory cytokine production by human T cells and monocytes (12).…”
Section: And E)mentioning
confidence: 99%
“…Given that ghrelin is expressed and secreted by T cells (12) and that the presence of growth factors in the thymic microenvironment is believed to play a critical role in T cell development (30), we next examined the expression of ghrelin and GHS-R in the thymus of mice of various ages. In comparison with 2-month-old mice, we observed an increase in the expression of thymic ghrelin mRNA in 4-month-old animals, followed by a subsequent decline in both ghrelin and GHS-R expression with progressive thymic aging (Figure 2A).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations